The impact of metacognitive strategy (MCS) in reading Arabic text among SMK Agama Students in Seremban - Mohd Sham Kamis; Maimun Aqsha Lubis; Norhayuza Mohamad; Aini Akmar Mohd Kasim; Aisyah Sjahrony (Penerbit Universiti Kebangsaan Malaysia, 2017)
Although the study of Arabic text reading is growing in Arab and other countries, it is still not as commonplace in Malaysia. Thus, this study focused on the use of Arabic metacognitive strategy (MCS) which was used by form 4 students at SMK Agama in Seremban. Apart from that, this article aimed to investigate the effects of MCS use of Arabic text in comprehension and Arabic vocabulary. Based on stratified sampling, 60 respondents were taken from SMKA in Seremban to undergo this study. This group was divided into two groups, with 30 in the experimental group and 30 in the control group. This study is a quantitative research and is a numericalbased research method that used the ANCOVA test. In this study, training was provided between pre-test and post-test. Eventually, after quasi-experimental studies were done, the finding showed that there is a significant difference in the Arabic comprehension and Arabic vocabulary post-test between the experimental group and control group. The experimental group indicated higher levels than the control group. This study contributes to the field of Arabic education from the perspective of the comprehension and vocabulary in MCS reading Arabic text.